Joshua Glen Thomas: capstone - Thomas, Joshua, artist (Colorado State University. Libraries, 2017)
The artist's statement: I work with digital and print media to create a marketable point or agenda. It can also be said that I create art work on demand, that must have a discernible marketing tagline, background illustrations, and designed layout for information. I always work with a sketchbook to continuously draw ideas or write notes for my design to fully realize its maximum potential (Potential through cohesive color, language, feeling, etc....). I have developed my design ability through exploring art but also through past career experiences. As a former Probation Officer with New Mexico and Larimer County, I learned my true passion was design and realized I needed to change careers. Returning afforded me the opportunity to understand my style of design, preferred art medium, and future aspirations. This restart allowed me to surround myself with inspiration and infuse my designs with a direction when I may not connect to the style or subject of a project. Variety is key to my success as a designer, I continually experiment with mediums and implement this into my methodology to form consistent work. Although I'm not afforded a specific art style, I do implement a modern style of design to give my background illustration a unified production to my body of work.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design